Genome‐wide association analysis reveals flowering‐related genes regulating rachis length in rice. (28th October 2016) - Hu, Yong; Huang, Yong; Zhang, Li; Zhao, Hu; Liu, Haiyang; Xing, Yongzhong; Bai, Xufeng
Abstract: Rachis length is correlated with panicle size in rice. Unveiling the genetic basis of rachis length is important for understanding the genetic regulation of panicle size. In this study, we performed a genomewide association study of rachis length using 529 rice accessions from two environments. In total, 20 loci were identified for rachis length and distributed across the 12 chromosomes except for chromosomes 2 and 5. Thirteen of the 20 loci were not linked to the cloned panicle size genes. Six flowering‐related genes, including the CCT domain‐containing genes Ghd7, Ghd7.1, Hd1, OsCCT1 and OsCO3 as well as Ehd1, were associated with rachis length in this study. These findings suggest that the network of these flowering‐related genes probably participates in the regulation of rachis length and thus affects panicle length and yield. Interestingly, haplotype analysis showed that OsCCT1 is a putative candidate gene which plays a key role in the variation of rachis length. Together, the genetic loci identified in this study could be used for rice breeding by marker‐assisted selection to improve grain yield.